ARDAN RADIO BANDUNG DIVERSIFICATION IN FACING MEDIA INDUSTRY BUSINESS COMPETITION IN THE DIGITAL ERA - Gissani, Muhammad Fikri; Nugraha, Adhyasa Henry (TOPLAMA, 2024)
The Internet has an impact and has implications for conventional broadcast media. The internet has become a new market in the current competitive media industry and has also caused cultural changes in society in using media. This research tells about the main concern is the diversification carried out by Ardan Radio in facing an industry business media in the digital era. The research method used in this research is a qualitative method with a case study approach according to Creswell. The research results show that it can be concluded that the business carried out by Ardan  Radio in facing media industry competition in the digital era is by diversifying through the  Five-O business strategy which  is adapted to  the environment. Diversification is carried out by Ardan with the Five-O concept. Five-O is a business strategy used by Ardan Radio to reach both markets, namely conventional and digital.